2010
DOI: 10.1111/j.1438-8677.2009.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and histochemical characterisation of two distinct poplar Melampsora leaf rust pathosystems

Abstract: In this study, we compared interactions of two Melampsora foliar rust species with poplar, which resulted in either limited or abundant pathogen proliferation. In the pathosystem exhibiting limited pathogen growth, a defence response was observed after invasion of poplar leaf tissues by the biotroph, with late and clear production of reactive oxygen species (ROS) and other products. Characterisation of the histological, biochemical and transcriptional events occurring in both pathosystems showed striking simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…Leaves LPI 8 and LPI 9 (leaf plastochron index, [132]) were used for all experiments from 1 m tall poplar trees (16 fully expanded leaves). Inoculation of leaf discs with Melampsora was conducted as previously described [133]. Briefly, disks of 2 cm in diameter were inoculated on the abaxial side with M. medusae f. sp.…”
Section: Methodsmentioning
confidence: 99%
“…Leaves LPI 8 and LPI 9 (leaf plastochron index, [132]) were used for all experiments from 1 m tall poplar trees (16 fully expanded leaves). Inoculation of leaf discs with Melampsora was conducted as previously described [133]. Briefly, disks of 2 cm in diameter were inoculated on the abaxial side with M. medusae f. sp.…”
Section: Methodsmentioning
confidence: 99%
“…Transcripts induced in LCM-isolated uredinia are more diverse and include several cell-cycle- and cell-rescue-related transcripts [9]. The induction of cell cycle transcripts is supportive of the intense cell division activity observed in the microdissected sporulation area, while cell-rescue- and defense-related transcripts might reflect an active defense from the rust fungus in response to the late activation of poplar reactions such as oxidative burst or expression of defense genes reported in compatible poplar-poplar rust interactions [5, 8] (Figure 3). Interestingly, transcripts accumulated in the sporulation area were predominantly detected in resting urediniospores and at 168 hpi in the time-course expression study [52].…”
Section: Poplar-poplar Rust Transcriptomics: Insights Into Plant Dmentioning
confidence: 96%
“…Cytological observations revealed a highly localized hypersensitive response (HR), with collapsed infected plant cells and accumulation of monolignols around infection sites after 48 hpi in the incompatible interaction [6, 7]. At later time points in the compatible interaction, anthocyanidins, lignin, pectin, and hydrogen peroxide accumulate around infection sites and likely participate in late defense responses and partial resistance in poplar [5, 8, 11]. …”
Section: The Populus/melampsora Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly we have also shown that mitogen activated protein kinases (MAPKs) are associated with poplar disease resistance against Melampsora rust [2]. New data obtained from various experimental approaches have directed our focus on two important families of transcription factors; the jasmonate ZIM-domain (JAZ) and Cys2/His2 zinc-finger protein (ZFP) families.…”
mentioning
confidence: 99%